Alternative oxidase 1 (Aox1) gene expression in roots of Medicago truncatula is a genotype-specific component of salt stress tolerance - Mhadhbi, Haythem; Fotopoulos, Vasileios; Mylona, Photini V.; Jebara, Moez; Mohamed, Elarbi Aouani; Polidoros, Alexios N. (My University, 2013)
Alternative oxidase (AOX) is the central component of the non-phosphorylating alternative respiratory pathway in plants and may be important for mitochondrial function during environmental stresses. Recently it has been proposed that Aox can be used as a functional marker for breeding stress tolerant plant varieties. This requires characterization of Aox alleles in plants with different degree of tolerance in a certain stress, affecting plant phenotype in a recognizable way. In this study we examined Aox1 gene expression levels in Medicago truncatula genotypes differing in salt stress tolerance, in order to uncover any correlation between Aox expression and tolerance to salt stress. Results demonstrated a specific induction of Aox1 gene expression in roots of the tolerant genotype that presented the lowest modulation in phenotypic and biochemical stress indices such as morphologic changes, protein level, lipid peroxidation and ROS generation. Similarly, in a previous study we reported that induction of antioxidant gene expression in the tolerant genotype contributed to the support of the antioxidant cellular machinery and stress tolerance. Correlation between expression patterns of the two groups of genes was revealed mainly in 48 h treated roots. Taken together, results from both experiments suggest that M. truncatula tolerance to salt stress may in part due to an efficient control of oxidative balance thanks to (i) induction of antioxidant systems and (ii) involvement of the AOX pathway. This reinforces the conclusion that differences in antioxidant mechanisms can be essential for salt stress tolerance in M. truncatula and possibly the corresponding genes, especially Aox, could be utilized as functional marker.
Keywords: Gene expression; Alternative oxidase; Functional markers; Medicago truncatula; Salt stress; Tolerance behaviour